Wearable technology for one health: Charting the course of dermal biosensing - Georgeta Vulpe; Guoyi Liu; Sam Oakley; Dimitrios Pletsas; Guanghao Yang; Rosa Dutra; Owen Guy; Yufei Liu; Mark Waldron; Joe Neary; Arjun Ajith Mohan; Sanjiv Sharma (Biosensors and Bioelectronics: X, 2024)
Over the last decade, a significant paradigm shift has been observed towards leveraging less invasive biological fluids—such as skin interstitial fluid (ISF), sweat, tears, and saliva—for health monitoring. This evolution seeks to transcend traditional, invasive blood-based methods, offering a more accessible approach to health monitoring for non-specialized personnel. Skin ISF, with its profound resemblance to blood, emerges as a pivotal medium for the real-time, minimally invasive tracking of a broad spectrum of biomarkers, thus becoming an invaluable asset for correlating with blood-based data. Our exploration delves deeply into the development of wearable molecular biosensors, spotlighting dermal sensors for their pivotal roles across both clinical and everyday health monitoring scenarios and underscoring their contributions to the holistic One Health initiative. In bringing forward the myriad challenges that permeate this field, we also project future directions, notably the potential of skin ISF as a promising candidate for continuous health tracking.Moreover, this paper aims to catalyse further exploration and innovation by presenting a curated selection of seminal technological advancements. Amidst the saturated landscape of analytical literature on translational challenges, our approach distinctly seeks to highlight recent developments. In attracting a wider spectrum of research groups to this versatile domain, we endeavour to broaden the collective understanding of its trajectory and potential, mapping the evolution of wearable biosensor technology. This strategy not only illuminates the transformative impact of wearable biosensors in reshaping health diagnostics and personalized medicine but also fosters increased participation and progress within the field. Distinct from recent manuscripts in this domain, our review serves as a distillation of key concepts, elucidating pivotal papers that mark the latest advancements in wearable sensors. Through presenting a curated collection of landmark studies and offering our perspectives on the challenges and forward paths, this paper seeks to guide new entrants in the area. We delineate a division between wearable epidermal and subdermal sensors—focusing on the latter as the future frontier—thereby establishing a unique discourse within the ongoing narrative on wearable sensing technologies.